Developments in Brazil-United States Tax and Anti-Corruption Enforcement Cooperation - Zagaris, Bruce (Revista Científica do CPJM, 2022)
This article discusses two selected areas of Brazil-United States enforcement cooperation: taxation and anti-corruption. The two governments have made significant progress in strengthening enforcement cooperation in both areas. However, they need to do much more to keep pace with the amount of gaps that exist and will continue to increase as a result of globalization. The Internet, free trade, and the easy movement of people have made it possible to move money, contraband, ideas, and persons over boundaries and sovereignty at incredible speeds. Similarly, environmental issues, such as climate control and pandemics, become global issues on a regular basis. Hence, governments and law enforcement are challenged to be innovative in increasing cooperation while still adhering to international human rights and due process.